3D hydrogen-bonded network built from copper(II) complexes of 1,3-propanediamine - Legendre, Alexandre O. [UNESP]; Andrade, Fabiana C. [UNESP]; Ananias, Sandra R. [UNESP]; Mauro, Antonio Eduardo [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Santos, Regina H. A.; Ferreira, Janaina G.; Martins, Fabiane R. (Soc Brasileira Quimica, 2006)
The reaction of Cu(NO3)(2).3H(2)O with 1,3-propanediamine (pn), in the presence of NaN3, afforded a 1:1 co-crystal formed by [Cu(NO3)(2)(pn)(2)] and [Cu(N-3)(NO3)(pn)(2)] (1 and 2), which were characterized by elemental analysis, IR spectroscopy and single crystal X-ray diffraction. In both compounds, the copper(II) centers are in a distorted octahedral environment, formed by four N atoms of two bidentate pn ligands in the basal plane, whereas the axial bonds are formed by two O atoms from the nitrate ligands in 1 and one O atom from the nitrate ligand and one N atom from the azide ion in 2. The asymmetric unit of the crystal consists of two crystallographically independent 1 and 2 complexes, which are held together in a 3D network by a series of N - H center dot center dot center dot O and N - H center dot center dot center dot N hydrogen bonds, as well C - H center dot center dot center dot O interactions. New supramolecular synthons are identified by the occurrence of two geometrically distinct molecular recognition patterns involving the NO3- ion and amino groups from pn ligands.
Keywords: copper(II) complexes; hydrogen bonds; supramolecular chemistry